DYNAMICS OF DISSENT AND WHISTLEBLOWING: CONCEPTUALIZATION AND THE WAY AHEAD - Halis, Denis de Castro (Juris Poiesis - Qualis A3, 2021)
This article"s overall aim is to reflect on dissent and its dynamics and to highlight connections between dissent and whistleblowing. The article does not contain a strictly legal approach based on existing criminal statutes. It expresses a socio-legal and conceptual perspective useful for further tracing important parallels between dissent and whistleblowing. It is built around four core sections in which whistleblowing is seen under the light of dissent. "Dissent: a foundational rather than a disputed concept"; "Establishing the concept of dissent"; "Dissenters as potential catalysts of changes"; "The way ahead for dissent and whistleblowing". These sections advance three arguments. Dissent and whistleblowing are much used but very ambivalent terms. Their lack of clarity does not contribute to discussions about their importance and regulation. Dissent, dissenters, and whistleblowers can be important catalysts of societal changes. A whistleblower is, by definition, a dissenter who, for whatever reasons, brings to the daylight what was not known by most. It is useful, thus, to study whistleblowers in relation to dissenters.